Delineation of the Clinical, Molecular and Cellular Aspects of Novel JAM3 Mutations Underlying the Autosomal Recessive Hemorrhagic Destruction of the Brain, Subependymal Calcification, and Congenital Cataracts. Issue 3 (18th February 2013) - Akawi, Nadia A.; Canpolat, Fuat E.; White, Susan M.; Quilis‐Esquerra, Josep; Morales Sanchez, Martin; Gamundi, Maria José; Mochida, Ganeshwaran H.; Walsh, Christopher A.; Ali, Bassam R.; Al‐Gazali, Lihadh
<x xml:space="preserve">Abstract</x> Mutations in Junctional adhesion molecule 3 (JAM3) cause the recessive syndrome involving hemorrhagic destruction of the brain, subependymal calcification, and congenital cataracts. T2‐weighted axial brain MRI of a patient reveals multifocal intraparenchymal hemorrhages of varying ages leading to calcifications (arrows) as well as intraventricular hemorrhage (asterisks). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>